Genital Mycoplasma and Chlamydia trachomatis infections in patients with genital tract infections attending a tertiary care hospital of North India - Karnika Saigal; Benu Dhawan; Jyoti Rawre; Neena Khanna; Rama Chaudhry (Wolters Kluwer Medknow Publications, 2016)
Limited data are available on the prevalence of genital mycoplasmas and Chlamydia trachomatis (CT) among Indian patients with genital tract infections. The objectives of the study were to determine the prevalence of Ureaplasma urealyticum (UU), Mycoplasma hominis (MH), Mycoplasma genitalium (MG), and CT in patients with genital tract infections. The antimicrobial susceptibilities of UU and MH were also assessed. Endocervical swabs/urethral swabs and first void urine samples of patients (n = 164) were collected. UU and MH were detected by culture and multiplex polymerase chain reaction (PCR). MG and CT were identified by PCR. Ureaplasma isolates were further biotyped and serotyped. Antimicrobial susceptibility was done by microbroth dilution method. UU, MH, MG, and CT were detected in 15.2%, 5.4%, 1.2%, and 6% patients, respectively. Ureaplasma parvum serovar 3/14 was the most prevalent. All isolates of UU and MH were uniformly susceptible to doxycycline and josamycin. Routine screening for these pathogens and antimicrobial susceptibility testing is warranted to prevent sequel of infections and formulate treatment guidelines.